Pelatihan Pembuatan Briket dari Limbah Kulit Kopi Berbasis Aset Lokal untuk Pemberdayaan Masyarakat Desa Jetak - Binuri Khoirun Niawati; Chintya Ayu Wulandari; Intan Nurlaila; Isniyatin Faizah (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
Coffee husk is an abundant agricultural by-product generated during post-harvest coffee processing, yet its utilization at the community level remains limited. This community service program aimed to enhance community empowerment through training on producing biomass briquettes from coffee husk using the *Asset Based Community Development* (ABCD) approach in Jetak Village, Montong District, Tuban Regency. The program employed qualitative descriptive methods through observation, semi-structured interviews, documentation, and participatory evaluation. Program implementation followed the ABCD stages, including asset identification, community engagement, training, hands-on practice, mentoring, and evaluation. The results demonstrated that the training successfully improved participants' knowledge and practical skills in converting coffee husk into biomass briquettes through carbonization, grinding, binder mixing, molding, and drying processes. The program also transformed community perceptions of coffee husk from agricultural waste into a valuable local resource with economic and environmental benefits. Furthermore, the initiative strengthened community participation, encouraged collaboration among stakeholders, and created opportunities for developing community-based microenterprises. Overall, the ABCD approach proved effective in optimizing local assets, promoting circular economy practices, reducing agricultural waste, and supporting sustainable rural development through community-driven innovation based on local resources.